Feasibility of personalized circulating tumor DNA detection in stage II and III melanoma. Issue 3 (5th June 2023) - Brunsgaard, Elise K.; Bowles, Tawnya L.; Asare, Elliot A.; Grossmann, Kenneth; Boucher, Kenneth M.; Grossmann, Allie; Jackson, Julie A.; Wada, David A.; Rathore, Richa; Budde, Griffin; Grandemange, Andrew; Hyngstrom, John R.
Abstract : The objective of this study was to evaluate the feasibility of developing personalized, tumor-informed assays for patients with high-risk resectable melanoma and examine circulating tumor DNA (ctDNA) levels in relation to clinical status. Pilot prospective study of clinical stage IIB/C and resectable stage III melanoma patients. Tumor tissue was used to design bespoke somatic assays for interrogating ctDNA in patients' plasma using a multiplex PCR (mPCR) next-generation sequencing (NGS)-based approach. Plasma samples for ctDNA analysis were collected pre-/post-surgery and during surveillance. Out of 28 patients (mean 65 years, 50% male), 13 (46%) had detectable ctDNA prior to definitive surgery and 96% (27/28) tested ctDNA-negative within 4 weeks post-surgery. Pre-surgical detection of ctDNA was significantly associated with the later-stage ( P  = 0.02) and clinically evident stage III disease ( P  = 0.007). Twenty patients continue in surveillance with serial ctDNA testing every 3–6 months. With a median follow-up of 443 days, six out of 20 (30%) patients developed detectable ctDNA levels during surveillance. All six of these patients recurred with a mean time to recurrence of 280 days. Detection of ctDNA in surveillance preceded the diagnosis of clinical recurrence in three patients, was detected concurrent with clinical recurrence in two patients and followed clinical recurrence in one patient. One additional patient developed brain metastases without detection of ctDNA during surveillance but had positive pre-surgical ctDNA. Our results demonstrate the feasibility of obtaining a personalized, tumor-informed mPCR NGS-based ctDNA assay for patients with melanoma, particularly in resectable stage III disease.